ECOLOGY AND EVOLUTION OF HIGHLY PATHOGENIC AVIAN INFLUENZA H5N1 IN RUSSIA (2005-2012) - K. A. Sharshov (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Russia covering a large part of Eurasia is of special interest for influenza virus ecology and evolution. The importance of this region has been confirmed by the previous outbreaks of HPAI H5N1 among wild birds from 2005 to 2010. Avian influenza virus surveillance is an important task prior the fundamental study and introduction. these data in practice. The article contains detailed comparative virological, molecular, pathogenic characteristics of H5N1 viruses isolated in Russia. Some molecular-epidemiological aspects are discussed. This study demonstrates the need for ongoing surveillance to detect new variants of influenza viruses and. facilitate prevention of outbreaks.